Reflective professionalism: interpreting CanMEDS' “professionalism” - Verkerk, M A (BMJ Group, 2007)
Residency training in the Netherlands is to be restructured over the coming years. To this end a general competence profile for medical specialists has been introduced. This profile is nearly the same as the Canadian CanMEDS 2000 model, which describes seven general areas of medical specialist competence, one of which is professionalism. In order to establish a training programme for residents and their instructors based on this competence, it is necessary to develop a vision that does justice to everyday medical practice. The two most prevailing views of professionalism—as personal, or as a behavioural characteristic—fall short of this. Only when professionalism is understood as reflective professionalism does it encompass the fundamental contextuality of medical treatment. This means that the focus of training and assessment must be shifted to accountability for treatment.